Notas sobre la vegetación de Andalucía. V. - Pérez Latorre, Andrés V.; Cabezudo, Baltasar (Acta Botanica Malacitana, 2003)
Short notes about Andalusian vegetation. V. Palabras clave. Vegetación, sintaxonomía, Pin guicula, Cistus laurifolius, Andalucía, España. Key words. Vegetation, syntaxonomy, Pinguicula, Cistus laurifolius, Andalusia, Spain.